Community harmony strengthening through selapanan mentoring of Badko TPQ in margolelo village - Ahmad Saichu; Nilma Afada; Muhammad Sulthon Maulana Ilham; Aisyah Mutiaramadhan (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Badko TPQ (Al-Qur'an Education Park Coordinating Board) activities in Margolelo Village are a routine tradition that is carried out every 35 days. This activity not only aims to increase religious understanding, but also acts as a means of strengthening harmony between residents. Through intensive assistance, it is hoped that this selapanan activity can become an effective medium for strengthening social relations and community harmony. This article discusses the mentoring process, the resulting impacts, and strategies for strengthening community harmony through Badko TPQ selapanan activities. The method used is a participatory approach involving community leaders, TPQ administrators, and Selapanan congregation. The results show that the Selapanan Badko TPQ activities succeeded in increasing the solidarity and harmony of the Selapanan Badko congregation in Margolelo Village